Thymoquinone inhibits growth of human medulloblastoma cells by inducing oxidative stress and caspase-dependent apoptosis while suppressing NF-jB signaling and IL-8 expression - Ashour, Abdelkader Elbadawy Abbas; Ahmed, Atallah F.; Kumar, Ashok; Zoheir, Khairy M. A.; Aboul-Soud, Mourad A.; Ahmad, Sheikh F.; Attia, Sabry M.; Abd-Allah, Adel R. A.; Cheryan, Vino T.; Rishi, Arun K. (Springer US, 2016)
Medulloblastoma (MB) is the most common malignant brain tumor of childhood. The transcription factor NF-κB is overexpressed in human MB and is a critical factor for MB tumor growth. NF-κB is known to regulate the expression of interleukin-8 (IL-8), the chemokine that enhances cancer cell growth and resistance to chemotherapy. We have recently shown that thymoquinone (TQ) suppresses growth of hepatocellular carcinoma cells in part by inhibiting NF-κB signaling. Here we sought to extend these studies in MB cells and show that TQ suppresses growth of MB cells in a dose- and time-dependent manner, causes G2M cell cycle arrest, and induces apoptosis. TQ significantly increased generation of reactive oxygen species (ROS), while pretreatment of MB cells with the ROS scavenger N-acetylcysteine (NAC) abrogated TQ-induced cell death and apoptosis, suggesting that TQ-induced cell death and apoptosis are oxidative stress-mediated. TQ inhibitory effects were associated with inhibition of NF-κB and altered expression of its downstream effectors IL-8 and its receptors, the anti-apoptotic Bcl-2, Bcl-xL, X-IAP, and FLIP, as well as the pro-apoptotic TRAIL-R1, caspase-8, caspase-9, Bcl-xS, and cytochrome c. TQ-triggered apoptosis was substantiated by up-regulation of the executioner caspase-3 and caspase-7, as well as cleavage of the death substrate poly(ADP-ribose)polymerase. Interestingly, pretreatment of MB cells with NAC or the pan-caspase inhibitor zVAD-fmk abrogated TQ-induced apoptosis, loss of cyclin B1 and NF-κB activity, suggesting that these TQ-mediated effects are oxidative stress- and caspase-dependent. These findings reveal that TQ induces both extrinsic and intrinsic pathways of apoptosis in MB cells, and suggest its potential usefulness in the treatment of MB.